The constitutional justice system in Mexico and the judicial reform - Ortiz Mayagoitia, Guillermo I. (2007)
The attachment to the Constitution is an unquestionable advance in the consolidation of the government of law, and strength of the democracy. The political field, from the democratically point of view is the result of the collective exercise of many political and civil rights. Is for that reason that is so important its constitutional defense in a impartial form, so that judicial acting in the political field generates certainty from the «technique» and the jurisprudence, leaving the political field where it corresponds. The increase in the demand of justice illustrates the importance of counting on the mechanisms that have been added to the system of constitutional justice; orients the effort of the justice administration and can help us to always value the importance of the real political forums and make them have greater exigency and freedom to agree and to disagree always with the endorsement of a system of reliable justice.